A Role for Global DNA Methylation Level and IL2 Expression in the Transition From Acute to Chronic Low Back Pain - Eller, Olivia C.; Glidden, Nicole; Knight, Brittany; McKearney, Noelle; Perry, Mallory; Bernier Carney, Katherine M.; Starkweather, Angela; Young, Erin E.; Baumbauer, Kyle M. (Frontiers in Pain Research, 2021)
Objectives: The transition from acute low back pain (aLBP) to chronic LBP (cLBP) results from a variety of factors, including epigenetic modifications of DNA. The aim of this study was to (1) compare global DNA (gDNA) methylation and histone acetylation at LBP onset between the aLBP and cLBP participants, (2) compare mRNA expression of genes with known roles in the transduction, maintenance, and/or modulation of pain between the aLBP and cLBP participants, (3) compare somatosensory function and pain ratings in our participants, and (4) determine if the aforementioned measurements were associated. Methods: A total of 220 participants were recruited for this prospective observational study following recent onset of an episode of LBP. We retained 45 individuals whose gDNA was of sufficient quality for analysis. The final sample included 14 participants whose pain resolved within 6 weeks of onset (aLBP),15 participants that reported pain for 6 months (cLBP), and 16 healthy controls. Participants were subjected to quantitative sensory testing (QST), blood was drawn via venipuncture, gDNA isolated, and global DNA methylation and histone acetylation, as well as mRNA expression of 84 candidate genes, were measured. Results: Individuals that develop cLBP display multimodal somatosensory hypersensitivity relative to aLBP participants. cLBP participants were also hypomethylated in comparison, which was negatively correlated with interleukin-2 (IL2) mRNA expression. Discussion: cLBP is characterized by somatosensory hypersensitivity, global DNA hypomethylation, and higher IL2 expression level compared to those whose pain will resolve quickly (aLBP). These results suggest potential diagnostic and therapeutic relevance for DNA methylation and IL2 expression in the pathology underlying the transition from acute to chronic LBP.